Long-term clinical outcomes of differentiated thyroid cancer patients with biochemical incomplete response after initial radioiodine therapy, a single-center, retrospective analysis - Wang, Congcong; Han, Peihang; Qin, Guohua; Li, Yutian; Wang, Xufu (Frontiers in Endocrinology, 2026)
BackgroundLittle is known regarding parameters predicting progressive disease (PD) for differentiated thyroid cancer (DTC) patients exhibiting biochemical incomplete response (BIR) after initial radioiodine (RAI) therapy. The aim of this study was to evaluate the long-term clinical outcomes of BIR patients and to establish the determinants of PD.Materials & methods172 DTC patients who were classified as BIR after initial RAI therapy between January 2010 to December 2023 in the Affiliated Hospital of Qingdao University were analyzed. All patients were received only one standardized RAI therapy. At the last follow-up, BIR patients were divided into the PD group and the non-progressive disease (NPD) group. PD was defined as the emergence of a new structural lesion or a ≥25% increase in thyroglobulin level. Univariate and multivariate Cox regression models were employed to identify independent risk factors associated with PD. Meanwhile, progression-free survival (PFS) for BIR patients were also assessed.ResultsAfter a median follow-up of 48.6 months, 40.1% (69/172) patients experienced PD. AJCC T stage (T1-T3a or T3b-T4; HR:2.073, 95%CI: 1.054-4.076, P = 0.035) and stimulated thyroglobulin (sTg, sTg< 50.0 ng/mL or sTg≥ 50.0 ng/mL; HR: 3.056, 95%CI: 1.655-5.644, P<0.001) were verified to be the independent predictive factors of PD. The median PFS of BIR patients was 64.4 months and the 5-year PFS rate was 60.4%.ConclusionsTg≥50.0 ng/mL and T3b-T4 stage are robust, clinically accessible markers identifying PD among BIR patients, warranting intensified surveillance and potentially earlier therapeutic reconsideration.